Pengaruh Dana Alokasi Umum, Pendapatan Asli Daerah dan Dana Alokasi Khusus terhadap Kemiskinan dengan Pertumbuhan Ekonomi sebagai Variabel Intervening Tahun 2015-2019 - Helena Louise Panggabean; Danarti Hariani; A. Yanuar B (Owner : Riset dan Jurnal Akuntansi, 2022)
Poverty is an important indicator to see  the welfare of a country. Papua is a province in Indonesia that has the highest number of poor people. The purpose of this study is to determine the factors that influence the level of poverty in Papua Province, so that it can be a reference for the government in efforts to overcome poverty, especially in Papua. This study uses quantitative research methods and uses secondary data obtained from the annual report of the Province, the Director General of Balance, Ministry of Finance, and BPS Papua Province. The data analysis used is panel data regression analysis. The results show that there is a significant effect of General Allocation Fund and Special Allocation Fund on Economic Growth, while Regional Original Income does not have a significant effect on Economic Growth. Other results also show that Economic Growth, Regional Original Income, and Special Allocation Funds have a significant effect on poverty, while the General Allocation Fund does not have a direct effect on poverty. The results of the mediation test show that economic growth is not able to mediate the relationship between the variables of the General Allocation Fund, Regional Original Income and the Special Allocation Fund on Poverty.